The Analysis of the Concept of “Spirituality” and the Emergence of Different Approaches in Dictionaries and Modern Scientific Literature - Mohira Rasulovna, Saidova; Khalima Aripovna, Aripova; Dilrabo Askarovna, Ubaydova; Dilfuza Kamilovna , Ergashova; Nasiba Almasovna, Shermukhamedova (International Journal of Psychosocial Rehabilitation, 2020)
After Uzbekistan gained independence, the "spirituality" was analyzed and studied as a scientific concept. First of all the question was "What is spirituality? “Specialists of all social and humanitarian spheres (sciences, language, literature, history, religious studies, sociology, ethics, aesthetic), who play an important role in enriching the spiritual world of man and society, have faced the challenge of finding a scientific answer. It is noteworthy that this notion has not been well-grounded in the Uzbek Philosophical Dictionary of the Soviet period. However, the scope of the use of the concepts "spirituality" and "spiritual" derived from its essence has been enlarged and their vocabulary and terminological meaning are so enriched that it is necessary to study spirituality as a separate scientific concept, culture, mind, thinking, worldview, spirit and artistic, political, moral values and so on, needs to determine their place in the conceptual system and analyze their relationship with them”